Arbuscular mycorrhiza influences carbon‐use efficiency and grain yield of wheat grown under pre‐ and post‐anthesis salinity stress. (11th June 2020) - Eroğlu, Ç. G.; Cabral, C.; Ravnskov, S.; Bak Topbjerg, H.; Wollenweber, B.
Abstract: Soil salinity severely affects and constrains crop production worldwide. Salinity causes osmotic and ionic stress, inhibiting gas exchange and photosynthesis, ultimately impairing plant growth and development. Arbuscular mycorrhiza (AM) have been shown to maintain light and carbon use efficiency under stress, possibly providing a tool to improve salinity tolerance of the host plants. Thus, it was hypothesized that AM will contribute to improved growth and yield under stress conditions. Wheat plants ( Triticum aestivum L.) were grown with (AMF+) or without (AMF−) arbuscular mycorrhizal fungi (AMF) inoculation. Plants were subjected to salinity stress (200 mm NaCl) either at pre‐ or post‐anthesis or at both stages. Growth and yield components, leaf chlorophyll content as well as gas exchange parameters and AMF colonization were analysed. AM plants exhibited a higher rate of net photosynthesis and stomatal conductance and lower intrinsic water use efficiency. Furthermore, AM wheat plants subjected to salinity stress at both pre‐anthesis and post‐anthesis maintained higher grain yield than non‐AM salinity‐stressed plants. These results suggest that AMF inoculation mitigates the negative effects of salinity stress by influencing carbon use efficiency and maintaining higher grain yield under stress. Abstract : Inoculation with arbuscular mycorrhizal fungi mitigated the negative effects of multiple salinity stress events by increasing carbon‐use efficiency and maintaining grain yield in spring wheat.